A FALSE START? ARE OLYMPIC ORGANISERS AND OFFICIAL SPONSORS SHOOTING THEMSELVES IN THE FOOT. AN INVESTIGATION INTO AMBUSH MARKETING REMEDIES - Andrew, Pinder (2012)
Ambush marketing has developed over the past 20 years and it appears that official sponsors are finally getting to grips with this practice. 3 main remedies have developed and have been proved to be very effective in combating ambushers. This investigation the effect such remedies had on the companies practising these remedies, and found that these remedies may have a detrimental affect on official sponsors.